(untitled) (PJDOL, 2023)
The evolution of mobile technology and its widespread use has prompted educators to research the use of mobile phones for education. Students of all ages use mobile phones not only for communication but also for entertainment, storage of data and accessing information. Many activities like photography have shifted to mobile, data storage has moved to mobiles, watching TV/movies is done on mobiles, internet is mostly accessed from mobiles. However, for learning purposes, use of mobile phones seems to be low.